O protagonismo de personagens negros em contos infantis: contribuições da análise do discurso crítica para o ensino de língua portuguesa em uma classe hospitalar - Sousa, Mauricéia Lopes Nascimento de (2016)
This research seeks to address the ethnic-racial theme and try to contribute to the implementation of the Brazilian Law nº 10.639/03. This law, despite having already completed a decade, still suffers resistance to its implementation in schools, failing to effectively contribute to the building of stronger identity of black children. In order to contribute to a more critical view of the ideological domination of race, the research was developed within a hospital class using tales, in which there are black characters to with that, and with the theoretical and methodological support to Critical Discourse Analysis - CDA (FAIRCLOUGH, 2001) that bring up issues related to the theme of strengthening of black identity in the social environment. As a result of our work, we could see that racist ideology is not questioned by the children, subjects of our research and that the CDA has a lot to contribute to the teaching and implementation of the law and the consequent change in the status quo. Finally, it was proved the subjection of students to the dominant ideology in regard to questions related to racial identity.